Prilaku Belajar dalam Konsep Pendidikan Islam - Nurlila Kamsi (STAI Bumi Silampari, 2020)
The view of Islamic education is something that is incumbent on humans, with human education gaining knowledge to form a much better behavior. in this study examines Islamic business education learning behavior in schools is expected to be able to shape personal piety and social piety at the same time. Learning behavior in the concept of Islamic education with literature research methods. Assess based on relevant sources. The results of this study that learning behavior is a matter of great concern for teachers to understand the theory and practice based on the a-Qur'an. And the formation of a Muslim personality and the achievement of learning objectives.